2015
DOI: 10.1039/c4cy01302f
|View full text |Cite
|
Sign up to set email alerts
|

In situ controllable assembly of layered-double-hydroxide-based nickel nanocatalysts for carbon dioxide reforming of methane

Abstract: The dual confinement effects from alumina and LDH precursors produced a new nanoplates-on-pore structure with a uniform distribution and smaller size of Ni nanoparticles (NPs) for the LDOs/γ-Al2O3, while enhanced catalytic performance and better resistance to sintering and coking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Structural properties of the catalysts were obtained by N 2 adsorption‐desorption analysis . The BET surface area, pore volume, and average pore diameter of as prepared catalysts are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural properties of the catalysts were obtained by N 2 adsorption‐desorption analysis . The BET surface area, pore volume, and average pore diameter of as prepared catalysts are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In sharp contrast to SiC supported catalysts, the diffraction peaks of nickel are weak, which may be resulted from the lower reduction degree. The diffraction peaks at 35.5°, 41.3°, 59.9°, 65.5°, and 71.7° are assigned to distinct peaks of face‐centered cubic 3C‐SiC (β‐SiC), and the peaks at 44.5° 51.8° and 76.4° are indexed to the face‐centered cubic nickel, which are related to the (111), (200) and (220) planes of nickel, respectively . The mean sizes of the nickel crystallites are shown in Table , as estimated from Ni(111) planes reflection using the Scherrer equation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The desorption peaks for the moderate and weak are allied to the adsorption of CO 2 by Lewis acid‐base pairings and surface hydroxide radical respectively. Decomposition of unidentate carbonates gives the high temperature peak . The introduction of promoters affected the type of basic sites and the peak intensities.…”
Section: Resultsmentioning
confidence: 99%
“…By this in-situ co-precipitation method, highly homogeneous dispersed and small particles of the active component and of large specific surface area provided by γ-Al 2 O 3 were achieved for these Ni/Co catalysts. Xu et al [25] reported an in situ controllable assembly procedure of Ni-based nanocatalysts derived from HTLcs. In this procedure, the mesoporous γ-Al 2 O 3 was activated in a solution of metal nitrates by urea hydrolysis under hydrothermal conditions.…”
Section: Co-precipitationmentioning
confidence: 99%